Determination of Flavonoids and Carotenoids and Their Contributions to Various Colors of Rose Cultivars (Rosa spp.) - Wan, Huihua; Yu, Chao; Han, Yu; Guo, Xuelian; Luo, Le; Pan, Huitang; Zheng, Tangchun; Wang, Jia; Cheng, Tangren; Zhang, Qixiang (Frontiers in Plant Science, 2019)
Rose is one of the most valuable ornamental crops worldwide. In this study, the composition of hydrophilic and lipophilic pigments in petals of six rose cultivars at seven developing stages was investigated by high performance liquid chromatography (HPLC) and mass spectrometry (MS). Four anthocyanins, twenty flavonols and ten carotenoids were detected in petals of tested cultivars. The major individual anthocyanins, flavonols and carotenoids were cyanidin/pelargonidin 3,5-diglucoside, kaempferol 3-O-rhamnoside, and (9Z)-violaxanthin, respectively. There were significant differences in pigments content in petals of different rose cultivars. The yellow petals of YI and GC had no or only a little anthocyanins, moderate amount of total flavonols, and the largest content of total carotenoids. The pink petals of PF, WQ, and YX had middling concentration of total anthocyanins, the largest concentration of total flavonols, and only little amount of carotenoids. The orange petals of CH had the highest content of total anthocyanins, the lowest content of total flavonols, and medium amount of total carotenoids. Correlation analysis showed that there were many pigments influencing petal colors, and multiple linear regression further indicated that pelargonidin 3,5-diglucoside, total anthocyanins and (9Z)-violaxanthin were the major factors. These investigations would contribute to understand the mechanism on the formation of flower colors and provide a theoretical basis for the breeding of flower color of rose. What's more, this study showed that the orange cultivar CH, the pink cultivar PF and the yellow cultivar YI had great potential as a natural source for the extraction of pelargonidin 3-O-glucoside, kaempferol 3-O-rhamnoside and (9Z)-violaxanthin, respectively.